(untitled) (Homoeopathy for All, 2022)
Homoeopathy is considered the second most popular and frequently used form of Traditional and Complementary Medicine (T&CM), according to World Health Organization (WHO). It is widely used in all WHO regions with a presence in about 100 countries worldwide. With legal recognition as an individual system of medicine in 42 countries, it is recognized as a part of complementary and alternative medicine in 28 countries.1